2020
DOI: 10.1016/j.ijpharm.2020.119057
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization by scattering and spectroscopic methods and biological evaluation of polymeric micelles of poloxamines and TPGS as nanocarriers for miltefosine delivery

Abstract: Structural characterization by scattering and spectroscopic methods and biological evaluation of polymeric micelles of poloxamines and TPGS as nanocarriers for miltefosine delivery

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 40 publications
(52 reference statements)
1
12
0
Order By: Relevance
“…MFS was reported earlier to integrate efficiently within LNC (>97%) most probably at the core/surfactant shell interface with the hydrophobic alkyl chain extending into the lipid core and the zwitter ionic group directed outwards, increasing the LNC structural integrity (Eissa et al., 2015 ). A similar orientation of MFS in polymeric micelles has been demonstrated (Puig-Rigall et al., 2020 ).…”
Section: Resultssupporting
confidence: 77%
“…MFS was reported earlier to integrate efficiently within LNC (>97%) most probably at the core/surfactant shell interface with the hydrophobic alkyl chain extending into the lipid core and the zwitter ionic group directed outwards, increasing the LNC structural integrity (Eissa et al., 2015 ). A similar orientation of MFS in polymeric micelles has been demonstrated (Puig-Rigall et al., 2020 ).…”
Section: Resultssupporting
confidence: 77%
“…With a low critical micelle concentration (CMC, 0.02% w / w ) and a micelle aggregation number close to 100, TPGS has been used as a safe adjuvant in the development of various colloidal formulations. Earlier studies, including ours, have demonstrated that it forms core-shell micelles which remain stable with temperature and concentration [ 12 , 13 , 14 , 15 ]. Apart from biosafety, TPGS possesses interesting biological properties relevant to drug delivery in cancer cells [ 16 ].…”
Section: Introductionmentioning
confidence: 82%
“…The plates were incubated for 24 h under the same conditions until promastigotes were phagocytized by macrophages. The extracellular parasites were removed by washing with medium, and plates were incubated with fresh medium containing 19-2.5 and 19-4LF peptides at 1 µg/mL [35]. Similarly, to analyze the effect of peptides in combination with leishmanicidal drugs (PM or Ampho B), infected macrophages were exposed to a mix containing 1 µg/mL of each peptide and 50 µM of PM or 0.025 µM of Ampho B; 72 h later, cells were washed with PBS, fixed with ice-cold methanol for 5 min and stained with Giemsa stain.…”
Section: Activity Against Intracellular Amastigotesmentioning
confidence: 99%